Effects of red light on sleep and mood in healthy subjects and individuals with insomnia disorder - Pan, Rong; Zhang, Guimei; Deng, Fangyi; Lin, Weifeng; Pan, Jiyang (Frontiers in Psychiatry, 2023)
Current Knowledge/Study Rationale:Studies on how light affects circadian rhythms and sleep have expanded to explore the role of monochromatic light. We aimed to test the hypothesis that red light affects sleep structure by influencing alertness, mood directly and indirectly, with the aim of providing a reference for the prevention and alleviation of ID and its complications.Red light can increase subjective alertness, anxiety, and negative emotions in both healthy subjects and people with ID, which can affect sleep directly or indirectly via the mediating effect of negative emotions. These findings provide solid evidence for the selection of a control light level in biological experiments and reasonable lighting before bedtime.